Discovery of Novel Tyrosinase Inhibitors From Marine Cyanobacteria - He, Yifan; Suyama, Takashi L.; Kim, Hyunwoo; Glukhov, Evgenia; Gerwick, William H. (Frontiers in Microbiology, 2022)
Tyrosinase, an important oxidase involved in the primary immune response in humans, can sometimes become problematic as it can catalyze undesirable oxidation reactions. Therefore, for decades there has been a strong pharmaceutical interest in the discovery of novel inhibitors of this enzyme. Recent studies have also indicated that tyrosinase inhibitors can potentially be used in the treatment of melanoma cancer. Over the years, many new tyrosinase inhibitors have been discovered from various natural sources; however, marine natural products (MNPs) have contributed only a small number of promising candidates. Therefore, in this study we focused on the discovery of new MNP tyrosinase inhibitors of marine cyanobacterial and algal origins. A colorimetric tyrosinase inhibitory assay was used to screen over 4500 marine extracts against mushroom tyrosinase (A. bisporus). Our results revealed that scytonemin monomer (ScyM), a pure compound from our compound library and also the monomeric last-step precursor in the biosynthesis of the well-known cyanobacterial sunscreen pigment ‘scytonemin’, consistently showed the highest tyrosinase inhibitory score. Determination of the half maximal inhibitory concentration (IC50) further indicated that ScyM is more potent than the commonly used commercial inhibitor standard ‘kojic acid’ (KA) (IC50 of ScyM: 4.90 µM vs IC50 of KA: 11.31 µM). After a scaled-up chemical synthesis of ScyM as well as its O-methyl analog (ScyM-OMe), we conducted a series of follow-up studies on their structures, inhibitory properties, and mode of inhibition. Our results supported ScyM as the second case ever of a novel tyrosinase inhibitory compound based on a marine cyanobacterial natural product. The excellent in vitro performance of ScyM makes it a promising candidate for applications such as a skin whitening agent or an adjuvant therapy for melanoma cancer treatment.